Sustainability Disclosure in The Malaysian Construction Sector: The Effect of Community and Media Legitimacies - Majdi, Suria; Mohd Saleh, Norman; Abdullah, Maizatulakma; Alias, Norazlan (UI Scholars Hub, 2023)
Research Aims: The objective of the study is to examines the effects of stakeholder pressure on sustainability disclosure (SD). The study includes the effect of community on SD when company consider the media as one of the legitimate stakeholders. Design/Methodology/Approach: Stakeholder legitimacy is evaluated using SD via content analysis based on panel data sample from construction and property sector. Research Findings: It was found that legitimacy is an antecedent and has positive relationship with SD. Furthermore, this relationship between community legitimacy and SD is stronger when mediated by media legitimacy. Theoretical Contribution/Originality: This study shows the effects of legitimacy attribute on SD instead of the influence of stakeholders in general (regardless of the legitimacy concept) and the incremental value for companies to include the interest of the media in SD apart from the communities alone. Managerial Implications in the South East Asian Context: It guides managers in forming a comprehensive stakeholder engagement plan and budget to increase company value. This illustrates to the managers the motivation behind making disclosures about the media in the SD more so in this rapid social media where fake and misleading information threaten the public trust in Southeast Asian. Research Limitations & Implications: The study does not include power and urgency factors along with legitimacy.